Formulation Design and Cell Cytotoxicity of Curcumin-Loaded Liposomal Solid Gels for Anti-Hepatitis C Virus - Helmy Yusuf; Erlyn K. D. D. Novitasari; Ni L. W. Purnami; Adhe W. Mahbub; Retno Sari; Dwi Setyawan (Advances in Pharmacological and Pharmaceutical Sciences)
Backgrounds. Curcumin (CUR) is a low-molecular-weight polyphenolic substance obtained from the tuber part of Curcuma species. Anti-inflammatory and anti-hepatitis C virus (HCV) activities have been associated with CUR. However, its poor aqueous solubility and low systemic bioavailability have been the challenges in improving the therapeutic efficacy of curcumin. Aim. The study aimed to produce CUR-loaded liposomal solid gels as anti-HCV delivery systems. Parameters including the physical characteristics and the cell cytotoxicity properties were evaluated. Methods. The freeze-drying technique was applied to manufacture the CUR-loaded liposomal solid gels. Scanning electron microscopy (SEM), X-ray diffractometry (XRD), and differential thermal analysis (DTA) were involved to reveal the characteristics of the solid gels. Such characteristics were as follows: the morphology and the microscopic structure of the solid gels, the crystallinity structure of the curcumin, and the thermal properties of the mixtures. Furthermore, their cell cytotoxicity was investigated using a Huh7it cell line. Results. The SEM images confirmed that curcumin liposomes were intact and trapped in the solid gel matrix. The XRD data showed flat patterns diffractograms of the formulations, confirming the transformation of CUR from crystalline to amorphous form. The DTA thermograms showed a single melting endothermic peak at a higher temperature around 200°C, indicating a single-phase transition of the mixtures. The XRD and DTA data revealed the molecular dispersion of CUR in the developed formulations. The cytotoxicity data provided as cell cytotoxicity 50 (CC50) for all formulations were ≥25 mg. These data confirmed that the developed liposomal solid gels were not cytotoxic to Huh7it cell line, indicating that the anti-HCV activity would be through a specific pathway and not by its toxicity. Conclusion. The CUR-loaded liposomal solid gels exhibited the potential and offered an alternative dosage form to improve the therapeutic efficacy of curcumin as an anti-HCV.